The Use of BBC (Box, Board, and Comics) Media in The Systems of Linear Equation - P D Widyastuti; M Mardiyana; D R S Saputro (Universitas Sebelas Maret, 2017)
Mathematics is one of the lessons in school. Starting from elementary school, junior high school, senior high school, even college. Mathematics is abstract and identic with numbers, so the author guessed that maybe this is the reason why students consider that mathematics is a difficult lesson. In fact, the learners deliver the material step by step. First, the teacher introduced something concrete to the students (related to the surrounding environment). After that, teacher introduced something more abstract to the students. Sometimes, the transition from concrete to abstract become the problem in the learning process. One of the materials that convert concrete to abstract is systems of linear equations in 8th grade because in this stage students are introduced to more coefficients and variables. This article will discuss how to use media in the form of BBC (Box, Board, and Comics) on systems of linear equations. This research is about Research and Development (R &D). The procedures of comics followed the ADDIE model which included analysis, design, development, implementation, and evaluation. This research aims to create a valid media based on the validation by the and students’ responses which can be proven that BBC (Box, Board, and Comics) media are interesting and worthy to use in the classroom.